Inclusive Communities A Critical Reader - Azzopardi, Andrew.; Azzopardi, Andrew.; Grech, Shaun.; Grech, Shaun. (Studies in Inclusive Education, 2012)
The term "Inclusive Communities" has increasingly featured in recent years, at policy, practice and theoretical levels, drawing from different disciplinary standpoints. Much of this has been spurred by efforts at understanding the exclusions confronted by certain populations, to develop the notion of and mechanisms by which communities can include those who are marginalised and/or oppressed, and in some contexts to 'bring back' community as something real or imagined. In spite of this, this deceptive term remains shrouded in epistemological darkness, conveniently endorsed but often little theorised and less understood. This text provides an exciting introductory textbook, drawing academics, policy makers and activists from various fields to theorise, create new and innovative conceptual platforms and develop further the hybrid idea of inclusive communities.